Menumbuhkan Nilai-Nilai Pendidikan Agama Islam dengan Program Pemberdayaan MDT (Madrasah Diniyyah Taklimiyyah) Di Desa Candali - Prabowo, Muhammad Aras; Ikhwana, Fariha; Hululudin, Hululudin; Alamsyah, Arif; Allaudza’i, Hanif; Hidayani, Hidayani; Aryani, Habsyah Fitri (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2024)
This activity aims to improve the quality of Madrasah Diniyah Taklimiyyah (MDT) through empowerment carried out by the Community Service (Pengmas) team at the Indonesian Nahdlatul Ulama University (Unusia). MDT Empowerment is one of the Unaged Community Service programs in 2022. Madrasah Diniyah Taklimiyyah informs the Muslim community about the existence of religious education. In its growth it leads to reform of religious education itself. Madrasah Diniyyah as non-formal education is recognized by the government as stated in Government Regulation No. 55 of 2007 concerning Religion and Religious Education, which is an indication of the government's desire to collaborate with the community in developing religious education. This opens up a wider path for the development and strengthening of religious education carried out by the community through various programs of affirmation, convenience and various supports and assistance. Madrasah Diniyah is one of the characteristics of Islamic religious education which has experienced significant momentum since its inception.